PENGEMBANGAN PERANGKAT PERCOBAAN KONSEP FLUIDA STATIS UNTUK PEMBELAJARAN IPA FISIKA SMP - Putri, Nadia; Zulhelmi, Zulhelmi; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to produce a valid static fluid experiments device so it is can be used as a medium of Junior High School Science Physics Learning. The object of this study was an experimental device consisting of static fluid experimental tools and experimental guidebooks. The research data was obtained from the validation result by 3 lecturers of physics education program and 3 teachers of junior high school physics as validator. Validation is done through two stages, which is the validation phase I improvement and the validation phase II assessment. Data were analyzed descriptively to determine the value of the validity of experimental devices. The result of data analysis is obtained, the validation of experimental equipment evaluation 3,72 with very valid categories and the guidance book evaluation 3,66 with very valid categories. Based on data analysis, it can be concluded that static fluid experimental device developed can be declared valid and it is suitable to be used as a Science physics learning media for Junior High School.Keywords: Development, Experiment Tool, Static Fluid.